Disaster education, communication and engagement - Dufty, Neil (John Wiley & Sons, Inc., 2020)
"Disasters are socially-constructed and therefore the role of at-risk people and their communities in disasters is critical. Learning by these people and their communities before, during and after a disaster is paramount. This book is about learning that aims to help keep people safe and minimise damages in disasters. It focusses on disasters emanating from natural hazards"--